(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Psychologists are also responsible for the members of our society to be mature, active and able to deal with each other. After all, it is no secret that society benefits from people who are more moral, pious, and do not deviate from their position. The article presents deviant behavior, its causes and methods of elimination.